Toddlers learn and flexibly apply multiple possibilities. Issue 6 (7th September 2021) - Goddu, Mariel K.; Sullivan, J. Nicholas; Walker, Caren M.
Abstract: The ability to consider multiple possibilities forms the basis for a wide variety of human‐unique cognitive capacities. When does this skill develop? Previous studies have narrowly focused on children's ability to prepare for incompatible future outcomes. Here, we investigate this capacity in a causal learning context. Adults ( N  = 109) and 18‐ to 30‐month olds ( N  = 104) observed evidence that was consistent with two hypotheses, each occupying a different level of abstraction (individual vs. relational causation). Results suggest that adults and toddlers identified multiple candidate causes for an effect, held these possibilities in mind, and flexibly applied the appropriate hypothesis to inform subsequent inferences. These findings challenge previous suggestions that the ability to consider multiple alternatives does not emerge until much later in development.